Activation of mouse peritoneal macrophages in vitro or in vivo by recombinant murine gamma interferon inhibits the growth of Chlamydia trachomatis serovar L1. - Zhong, G M (1988)
Peritoneal mouse macrophages activated in vitro with recombinant murine gamma interferon (10 ng/ml) or in vivo (10 micrograms per mouse) showed a significant decrease in the growth and yield of Chlamydia trachomatis. The restriction of the growth of C. trachomatis paralleled the expression of Iad on the macrophages. Mice that received macrophages activated in vitro with recombinant murine gamma interferon showed a significant decrease in the yield of chlamydial infection-forming units from their spleens and peritoneal fluids.